Environmental Management in the Center of Smoked Fish Household Scale Karangsari Village, Tuban Regency - Nurma Chosiyana; Aminudin Afandhi; Harsuko Riniwati (Faculty of Fisheries and Marine Science, Brawijaya University, 2019)
This study aims to analyze the quality of the waters, the causes of the decline in environmental quality and planning strategies in managing the environment in the fish fog center in Karangsari Village, Tuban Regency. This type of research is a sequential explanatory design. The data analysis used in this study is qualitative analysis and quantitative analysis which includes water quality analysis and SWOT analysis. The results showed that the water quality in Karangsari Village was classified as a moderate pollutant. The causes of changes in environmental quality at the fish fog center are caused by people's behavior in disposing of waste, public awareness to treat waste, lack of handling of fish fumes, community efforts to protect the environment, group awareness in managing smoked fish, community needs for IPAL and fish fumigation without using chemical material. The planning strategy in managing the fish fog center environment through the matrix of internal strategic factors (IFAS) and the external strategic factor matrix (EFAS) at the horizontal axis coordinates (X) is 1.54 and the vertical axis (Y) is 1.30. The calculation is in quadrant I and the strategy that can be applied is the SO strategy that supports aggressive growth policies.